AI-DRIVEN QUALITY ASSURANCE IN SME CONSTRUCTION: AN IoT-BASED COST OPTIMIZATION CASE STUDY - Протопопова, Зінаїда (SWorldJournal, 2025)
The article presents an approach to automating quality control of construction works in small and medium–sized enterprises (SMEs) through the integration of Internet of Things (IoT) technologies and artificial intelligence (AI) methods. We developed a mon